Effect of Transglutaminase and Bacterial Concentrates on the Development of Functional and Technological Properties of Minced Meat - Svetlana Merenkova; Oksana Zinina; Olga Loretts; Olga Neverova; Pavel Sharaviev (Polish Journal of Food and Nutrition Sciences, 2019)
The results of the effects of transglutaminase (TG) and bacterial concentrates (BC) of different strains of microorganisms on the functional and technological properties of minced meat obtained from beef trimming (80/20) are presented. A control and seven experimental samples of minced meat were obtained – three samples with the addition of 10% BC: Bifilact-Pro, Bifilact-AD, Bifilact-Kefir (S-Pro, S-AD, SK), a sample with the addition of 0.2% TG (S-TG) and three samples with simultaneous addition of 5% BC: Bifilact-Pro, Bifilact-AD, Bifilact-Kefir and 0.1% TG (S-Pro + TG, S-AD + TG, S-K + TG). The control and experimental samples were analyzed for: pH, water binding capacity (WBC), water holding capacity (WHC), cooking loss, as well as physicochemical and rheological properties. The highest WHC was observed in the S-TG samples during the 6–12 h of ripening, whereas in the S-Pro+TG, S-AD+TG and S-K+TG samples during the ripening period of 12–18 h. The data obtained correlated with an increase in the pH value in the samples during the indicated periods. Significant differences were noted in the changes in WBC and WHC when BCs were added to the minced meat, as dependent on the composition of the microorganism cultures. The lowest cooking losses were determined in the S-TG sample, i.e. 19.03–19.99% (p<0.05), whereas in the S-AD+TG and S-K+TG samples they reached 17.91–18.61% (p<0.05) and 18.96–19.58% (p<0.05), respectively. The most pronounced elastic properties were found in the samples with TG. Thus, the results showed that the combination of BC and TG demonstrates a synergistic effect on the functional and technological properties of meat systems.